Communication Behaviour of Street Children and Beggars in Makassar - Tuti Bahfiarti (Department Anthropology, Faculty of Social and Political Sciences Hasanuddin University., 2019)
The purpose of this reseach is to explore, and categorize verbal and non verbal communication behavior in the performances of street children and beggars in Makassar. This study explored the operational actions and motivations of street children and beggars who work the streets. This study uses a qualitative method that seeks to interpret the meaning of data to understand a community's social life. The ethnographic approach to communication studies focuses on studying the interactions and activities of individuals as social creatures in using verbal and non-verbal symbols. Primary data collection was carried out through in-depth interviews with 21 street children informants and beggars operating in three sectors, namely, the Panakukang/ Fly Over/Red Light Sector, the Losari Beach Platform Sector, and the Hertasning Sector. Non-participant observation by repeatedly observing themselves both verbally and non-verbally in performing actions and actions in front of benefactors. This study found verbal and non verbal communication behaviors that are displayed as a form of impression management on the front stage in attracting the sympathies of benefactors. Verbal communication behavior in the form of spoken and written language based on categorical finding verbal symbols of street children and beggars using three elements, namely the structure of the message, the style of the message, and the attractiveness of the message. Furthermore, the categorization of non-verbal communication behaviors is facial expressions, body movements (kinetic), physical appearance (body and manner of dress), and paralinguistic(vocalic).